PENTAHELIX MODEL FOR TOURISM COMMUNICATION BRANDING IN COASTAL COMMUNITIES RIAU PROVINCE, INDONESIA - ismandianto, ismandianto (Universitas Padjadjaran, 2026)
Bengkalis has significant tourism potential, closely linked to its rich local culture and religious traditions; however, this potential is hampered by a lack of meaningful cooperation between the local government and the local community, exacerbated by the suboptimal use of digital media in marketing efforts. This study focuses on an in-depth examination of the government’s discourse on tourism branding, which is primarily based on local cultural practices, religious beliefs and traditional knowledge, whilst identifying the factors that hinder or drive the success of these efforts, with the aim of creating a robust strategy for sustainable growth. Using a qualitative research approach centred on dynamic case studies, this research explores the complex relationships between government agencies, Pokdarwis, and tourists. Data has been carefully collected through in-depth interviews, participant observation, and detailed document analysis. The results show that government bodies have adopted an interactive two-way communication model, which includes direct interactions like focus group meetings and discussions, as well as indirect approaches such as social media and national tourism information systems. The SWOT analysis reveals that ecotourism and religious tourism have significant potential, while also highlighting that issues related to infrastructure and human resource capabilities are major weaknesses. Strategic suggestions recommend improving collaboration among stakeholders, making substantial investments in digital infrastructure, and integrating sustainable practices. The findings of this research offer a meaningful contribution by underscoring the importance of place branding and cross-border communication models in local settings, while also providing frameworks relevant to coastal areas across Indonesia.